INFLUENCE OF CERIUM ADDITION ON THE SYNTHESIS OF SOLIDS BASED ON PLATINUM SUPPORTED OVER ALUMINA-PILLARED CLAY - BARRERA-VARGAS, M.; A. ALMANZA, O.; CARRIAZO, J. G. (Scientia et Technica, 2007)
The present work shows the preparation and characterization of a set of solids by modification of a natural clay with Al, Ce and Pt. The characterization of the solids by X-ray diffraction (XRD) reveals the insertion of alumina pillars, whereas the subsequent impregnations of the pillared clay with Pt (II) or Ce (IV) do not lead to structural variations that can be observed by XRD. The characterization by nitrogen adsorption indicates that the incorporation of platinum species originates damages in the microporosity of the solid, while the addition of cerium prevents the deterioration of the textural properties